MULTICULTURAL POLITICAL COMMUNICATION IN SOCIAL CONFLICT MANAGEMENT - Abdul Rahman (Social Studies and Humanities Journal (SOSHUM), 2025)
The complexity of social conflict in multicultural societies is increasing due to the high dynamics of ethnicity, religion, and identity politics. In this context, political communication plays a strategic role in determining the direction of conflict escalation and de-escalation. This study analyzes how multicultural political communication strategies can mitigate, manage, and prevent conflict through message adaptation, inclusive framing, cross-cultural dialogue, and trust-building between political actors and community groups. The findings indicate that the effectiveness of political communication depends not only on the quality of the message but also on its alignment with the values, symbols, and local cultural identities that develop within the community. Communication strategies that are insensitive to the cultural context have been shown to increase the risk of misinterpretation and reinforce polarization. Conversely, strategies oriented toward cultural empathy can create a space for constructive dialogue and strengthen social cohesion. This study proposes the development of a theoretical model.Multicultural Political Communication for Conflict Managementas a new framework that can be used to explain how political communication can function as a more effective instrument for conflict management in multicultural societies. These findings make an important contribution to the development of political communication studies and government communication practices.